What traits do urology programs value in elective students? : A survey of Canadian selection committee members - Niakani, Sepehr; Nguyen, David-Dan; Aubé-Peterkin, Mélanie (Canadian Urological Association Journal, 2025)
INTRODUCTION: Electives strongly influence residency selection. While the CanMEDS framework outlines core competencies, the specific traits most valued by urology programs during electives remain unclear. METHODS: We surveyed selection committee members in Canadian urology residency programs. Using the CanMEDS framework, we developed 21 competencies and designed a best-worst scaling survey, where respondents selected the most and least important items from 21-question sets. A hierarchical Bayes model was used to calculate probability scores to rank each item and CanMEDS role. Scores reflect the likelihood of being chosen as most important. RESULTS: Thirteen respondents completed the survey (34% response rate). Traits related to professionalism, initiative, and reliability ranked highest. Specifically, “Demonstrating appropriate behavior through honesty, integrity, punctuality, and respect” (12.4% [95% credible interval (CI) 11.9, 13.0]) and “Seeking out responsibilities by helping with rounds, doing consults, and organizing patient handover and discharge” (9.7% [8.5, 10.9]) were top ranked. In contrast, “Incorporating evidence on health disparities in urology when presenting cases or research findings” (0.1% [0.0, 0.2]) and “Discussing barriers to care, such as cost and access, and proposing solutions during rounds when appropriate” (0.0% [0.0, 0.1]) were lowest ranked. Among CanMEDS roles, Professional (9.9%) and Leader (8.1%) ranked highest, while Health Advocate (0.2%) and Scholar (1.8%) ranked lowest. CONCLUSIONS: Canadian urology programs prioritize professionalism, initiative, and reliability during electives. In contrast, scholarly and advocacy competencies are viewed as less critical, possibly due to the short duration and clinical focus of electives. Our findings can guide students and programs in aligning expectations during urology electives.